1998
DOI: 10.1210/jcem.83.2.4529
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Penetrance of Primary Hyperparathyroidism in Multiple Endocrine Neoplasia Type 2A Families with Mutations at Codon 634 of theRETProto-Oncogene1

Abstract: Germline mutations of the RET proto-oncogene are responsible for multiple endocrine neoplasia type 2, including multiple endocrine type 2A (MEN 2A), type 2B (MEN 2B), and familial medullary thyroid carcinoma. The relationship between specific mutations and syndromic features has been established. In particular, the risk for pheochromocytoma and hyperparathyroidism (HPT) in MEN 2A patients is clearly associated with the presence of the RET mutation at a specific position, i.e. at codon 634. Also, a correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 0 publications
9
30
1
Order By: Relevance
“…Furthermore, the mutation-specific penetrance data in our study also showed higher penetrance of the C634R mutation than the C634Y mutation. Our data regarding HPT prevalence and age-related penetrance in C634R carriers agree with a previous report (24), which found higher HPT age-related penetrance in C634R carriers than in patients with any other amino acid exchange at codon 634; an individual comparison was not performed between specific amino acid substitutions at codon 634.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the mutation-specific penetrance data in our study also showed higher penetrance of the C634R mutation than the C634Y mutation. Our data regarding HPT prevalence and age-related penetrance in C634R carriers agree with a previous report (24), which found higher HPT age-related penetrance in C634R carriers than in patients with any other amino acid exchange at codon 634; an individual comparison was not performed between specific amino acid substitutions at codon 634.…”
Section: Discussionsupporting
confidence: 91%
“…Taking into account the findings of previous studies (13,23,24), and our own findings, we hypothesise, in agreement with others (10), that specific amino acid substitutions could change the protein biochemistry altering its function; thus, the C634R mutation could confer a higher penetrance of the MEN2A phenotype and more aggressive behaviour of MTC than the C634Y mutation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on data from the French MEN2 registry, 5.6-9.1% of germline mutations (running in 8-13 of 143 families) occur de novo in the parental germline (Schuffenecker et al 1997), replenishing the pool of index patients that screening programs seek to deplete. These countervailing effects may make it unfeasible to diminish the percentage of index patients below the spontaneous mutation rate of 5.6-9.1%.…”
Section: Population-based Effectiveness Of Dna-based Screening For Men2mentioning
confidence: 99%
“…Accordingly, in the younger sister of the patient, tests for pheochromocytoma and follow-up observations based on serum concentrations of parathyroid hormone and calcium performed on a yearly basis are warranted. It has also been reported that mutations of codon 634 are associated with the development of pheochromocytoma before the age of 5-10 years [18]. In addition, this mutation corresponds to the high-risk phase II group with respect to the degree of malignancy of MTC [6].…”
Section: Introductionmentioning
confidence: 85%